Digital Entrepreneurship and Women’s Economic Empowerment: Evidence from Community-Based Interventions among Poor Household Women in Punjab, Pakistan - Madiha Parvaiz; Sohail Anwar; Umair Tufail; Sufyan Ahmed (`, 2026)
Purpose: The research aims at assessing the efficacy of digital entrepreneurship, supported by community-based interventions, in fostering the process of economic empowerment among poor household women in Punjab, Pakistan. Design /Methodology/Approach: A quantitative survey design was applied where 355 women in low-income-earning families who were actively involved in community- based digital entrepreneurship programs were surveyed in a cross-sectional study. We used a structured questionnaire to assess the digital entrepreneurship participation, economic empowerment (financial autonomy, household decision-making power, and psychological confidence), and three moderators: digital literacy, ICT access, and family support. The direct effects, moderation, quality of measurement model, and predictive relevance were studied using Partial Least Squares Structural Equation Modeling (PLS-SEM) with bootstrapping (5,000 resamples). Newer analyses were multi-group analysis (MGA) and importance-performance map analysis (IPMA). Findings: Digital entrepreneurship has a strong positive direct influence on the economic empowerment of women (= 0.54, p < 0.001), and the variance it explains is 63% (R 2 = 0.63). This model has high predictive relevance (Q 2 = 0.41) and good fit (SRMR = 0.062). This relationship is strongly moderated and reinforced by digital literacy (= 0.14), ICT access (= 0.11), and family support (= 0.16). Among rural women, MGA indicates greater impact (= 0.61), whereas IPMA highlights family support as an area of high significance but with lower performance. Implications/Originality/Value: This paper is the first rigorous PLS-SEM evidence on the work of digital entrepreneurship in Pakistan that shows how digital entrepreneurship operates as a multidimensional empowerment mechanism through the facilitation of skills, infrastructure, and family acceptance. The results provide practical lessons to NGOs, policymakers, and development agencies to structure the integrated digital inclusion programs that can promote SDGs 5, 8, and 9. Contextual enablers should be alongside demand-side digital interventions to realise sustainable output of empowerment in conservative, low-income environments. Keywords: Digital Entrepreneurship; Women’s Economic Empowerment; Digital Literacy; ICT Access; Family Support; Community-Based Interventions; Capability Approach; Gender and Technology; Pakistan.